Directed hydrogenation of sulphoxides and sulphones - Price, D; Price, David (1992)
This thesis describes the synthesis of a number of hydroxy vinylsulphoxides and sulphones by a high pressure modification of the Baylis-Hillman reaction, together with their directed hydrogenation catalysed by rhodium catalysts. A detailed kinetic analysis of a number of the hydrogenation reactions carried out by numerical analysis is also presented. Chapter 1 serves as an introduction to directed hydrogenation and the chemistry of sulphur containing compounds. Chapter 2 details the synthesis of catalysts and substrates used in hydrogenation reactions. The use of high pressures to improve the performance of the Baylis-Hillman reaction is included. Chapter 3 details the products and the selectivity obtained in the hydrogenation of hydroxy vinylsulphoxides and sulphones. The kinetic resolution of 3-phenyl-2-(phenylsulphonyl)- propene-3-ol using a DiPAMP rhodium catalyst is described. Chapter 4 details the numerical analysis of the kinetics of the hydrogenation reactions of a number of hydroxy vinylsulphoxides and sulphones.